Implementation of Strategic Management in Improving the Quality of Education at MIS Terpadu Mutiara Hikmah - Umi Masnah Sihombing; Dwika Hanum Sagala; Siti Nur Aisah Solin; Apta Hafiz Sampurno; Wirahayu Wirahayu (Edumaspul: Jurnal Pendidikan, 2022)
This research focuses on strategic management in improving the quality of education at MIS Terpadu Mutiara Hikmah where the implementation of strategic management is seen from the aspects of planning, organizing, implementing and monitoring to improve an expected quality of education. Improving the quality of education is a process and educational outcomes that influence each other. In measuring the quality of education, it can be seen from an effective and maximum learning process, adequate facilities, professional teachers to support from various parties so that the quality of education can be better than before. So in this study the researcher wanted to find out how the implementation of strategic management in improving the quality of education at MIS Terpadu Mutiara Hikmah.